DESIGN AND CONSTRUCTION OF APPLICATION FOR SUBMISSION AND USE OF MEDICAL DEVICE NEEDS (Case Study of MITRA MEDIKA BANDAR KLIPPA HOSPITAL) USING PROTOTYPE METHOD - Nasution, Raisa Nadiratul Alfath; Zakir, Ahmad; Elhanafi, Andi Marwan (Cattleya Darmaya Fortuna, 2024)
This study aims to design a web-based application that supports the process of submitting and using medical device needs at Mitra Medika Bandar Klippa Hospital. This application is designed to make it easier for logistics admins to manage medical device stock, including adding and removing goods, and to make it easier for medical staff to submit device requests and monitor their submission status. The methodology used involves system requirements analysis, design, implementation, and system testing using the Black Box Testing method. The test results show that all application features, such as stock management, report printing, and submission status monitoring, function properly without any errors. User surveys show a satisfaction level of 75%, indicating that this application is effective in improving the efficiency of medical device management in hospitals.